Osteonecrosis of the jaw with pancytopenia in a patient receiving methotrexate for rheumatoid arthritis without antiresorptive or antiangiogenic agents: Report of a case. Issue 5 (September 2018) - Sato, Tsuyoshi; Okubo, Masahiko; Hayashi, Naoki; Yumoto, Megumi; Fukushima, Yosuke; Yoda, Tetsuya
Abstract: It is well known that osteonecrosis of the jaw is induced by the adverse effect of medication including bisphosphonates and anti-receptor activator of nuclear factor-kappa B ligand antibody. Recently, a few case reports showed that methotrexate is capable of inducing osteonecrosis of the jaw in the absence of antiresorptive or antiangiogenic agents. We herein introduce a case of osteonecrosis of the jaw with pancytopenia by low-dose methotrexate administration for rheumatoid arthritis. The patient of this case has been extracted teeth and subsequently suffered from the pain osteonecrosis of the jaw. Referring to our hospital, the patient was diagnosed as disseminated intravascular coagulation. Being received appropriate treatment, his condition was gradually recovered and he was discharged at thirty days after admission. We should bear this case in mind in examining patients being prescribed methotrexate.